REAL-TIME PATIENT SATISFACTION SURVEY IN THE OPHTHALMOLOGY DEPARTMENT OF A TERTIARY CARE HOSPITAL IN PAKISTAN: A TOOL FOR QUALITY IMPROVEMENT - SAJJAD , T; MUKHTAR, MT; NAVEED, H; RAO, MRQ; SHAMS, F; RAO, MS (Biological and Clinical Sciences Research Journal, 2024)
Patient satisfaction is a critical indicator of healthcare quality and is essential for improving service delivery in medical settings. Understanding patient satisfaction and the factors that contribute to it can help healthcare providers enhance patient experiences and outcomes. Objective: To assess patient satisfaction in the ophthalmology department and identify its contributing factors. Methods: A cross-sectional study was conducted in the Ophthalmology Department of Nishtar Medical University and Hospital, Multan, from February 2023 to February 2024. A total of 400 patients visiting the department were selected for the study. Patients’ demographic data and satisfaction levels were recorded using a questionnaire in both English and Urdu. The questionnaire included questions about waiting time, staff behavior, communication with specialists, and overall department satisfaction. Patients answered on a Likert scale from 1 (strongly disagree) to 5 (strongly agree). Statistical analysis was performed to calculate satisfaction percentages and confidence intervals. Results: Overall, 224 patients (56%, 95% CI: 50-60.5) reported satisfaction with the ophthalmology department. More than half of the participants expressed satisfaction with various aspects of hospital services, including healthcare (65%), specialist advice (55%), department hygiene (51%), advanced facilities (50%), and post-operative care (60%). However, satisfaction scores for waiting times were lower, ranging from 45% to 55%. Conclusion: Most patients were satisfied with the ophthalmology services provided at the hospital. However, there is room for improvement, particularly in reducing waiting times, to enhance patient care and satisfaction.